Intuitive eating and its relationship to physical activity, body mass index and eating behavior among university students. A case study - Musat, George Cosmin; Petcu, Damian; Georgescu, Adrian; Cazan, Florin; Voinea, Florin; Georgescu, Andreea; Savu, Catalin Vasile; Barna, Octavian; Banu, Ariela Elena; Plesea-Condratovici, Alina (Progress in Nutrition, 2024)
University years are a time of decline in diet quality, which may play a central role in weight gain. People’s eating behavior depends on a series of emotions such as joy, depression, anxiety, and sadness, so the choice of food and the frequency and quantity of meals do not depend exclusively on physiological needs. A series of studies have shown that intuitive eating may be helpful in the treatment of eating disorders and obesity. This cross-sectional study aims to establish if the concern for an intuitive diet is related to physical activity and if these two can lead to a lower body mass index and obesity prevention. The study was conducted in Romania on 1585 students (846 women and 739 men) aged 19 to 26 years. The questionnaire included four parts related to sociodemographic characteristics and anthropometric measurements (IES-2), IPAQ (PA), and HEI 2020 score. According to the scores, participants’ diets were categorized as “poor” (≤50), “needs improvement” (from 51 to 80), and “good” (> 80). Pearson correlation coefficients were calculated between HEI scores, BMI, PA, IES-2 total score, and IES-2 subscales for participants. Statistical analyses showed a significant correlation between HEI and the score of participants with BMI (r= -0.322; p < 0.01), PA (r= -0.734; p < 0.01), and IES-2 score (r= 0.654; p < 0.01). IES-2 scores were significantly inversely correlated with BMI (r= -0.341; p < 0.01). Also, the results of the correlation analyses showed a direct correlation with all subscales of IES-2 and HEI scores (p<0.05). The findings of this study reveal that intuitive eating is positively related to diet quality, weight status, and PA. Intuitive eating can offer a more holistic and long-term weight control approach than traditional body weight management strategies.